Coronary artery calcium score plays an important role for cardiovascular risk stratification in the statin benefit groups of asymptomatic individuals - Dong-Hyeon Lee; Ho-Joong Youn; Hae-Ok Jung; Kiyuk Chang; Yun-Seok Choi; Jung Im Jung (Lipids in Health and Disease, 2017)
Abstract Background The purpose of this study was to describe and analyze the relationship between statin benefit groups based on statin-intensity class of drugs and coronary artery calcium score (CACS) using multidetector computed tomography (MDCT) in an asymptomatic Korean population. Methods A total of 3914 asymptomatic individuals (mean age: 55 ± 10 years; male: female = 2649: 1265) who underwent MDCT for health examination between January 2009 and December 2012 were retrospectively enrolled. They were categorized into three groups based on statin-intensity class of drugs (high-intensity (n = 1284, 32.8%); moderate-intensity (n = 1602, 40.9%) and low-intensity (n = 931, 23.8%) statin therapy groups) according to the American College of Cardiology (ACC)/American heart Association (AHA) 2013 guideline and the relationship between CACS and statin benefit group was analyzed. The statin benefit group was defined as individuals who should be considered moderate- and high-intensity statin therapy. Results Ten-year atherosclerotic cardiovascular disease (ASCVD; 12.6 ± 5.3% vs. 2.9 ± 1.9%, p < 0.001) and CACS (98 ± 270 vs. 3 ± 2, p < 0.001) were significantly higher in the high-intensity group compared to the moderate-intensity statin therapy group. In the high-intensity statin therapy group, age [odds ratio: 1.299 (1.137–1.483), p < 0.001], male gender [odds ratio: 44.252 (1.959–999.784), p = 0.001], and fasting blood glucose [odds ratio: 1.046 (1.007–1.087), p = 0.021] were independent risk factors associated with CACS ≥300 on multivariate logistic regression analysis. Conclusions CACS on MDCT might be an important complementary tool for cardiovascular disease risk stratification. This study indicates that individualization of statin therapy as well as lifestyle modification will be useful in asymptomatic individuals, especially those in whom high-intensity statin therapy is required.